PERAN PEMBIAYAAN MUDHARABAH DALAM PENGEMBANGAN KINERJA USAHA MIKRO (Studi Kasus pada BMT Sumber Mulia, BMT Assaadah dan BMT Hubbul Wathon di Kabupaten Semarang) - Ernanda Kusuma Dewi; Widiyanto Widiyanto (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
The purpose of this study is to describe and analyze factors that supports the successful ofmudharabah financing of micro-enterprises performance. The sample in this study amountedto 52 members BMT Sumber Mulia, BMT Assaadah and BMT Hubbul Wathon mudharabahfinancing recipients and 10 BMT employees. This research is explanatory research. Thisresearch uses multiple linear regression analysis. The result of the analysis concludes thatmudharabah financing conducted by BMT Sumber Mulia, BMT Assaadah and BMT HubbulWathon have expanded its business based on sharia principles, mudharabah financing providedfor BMT members has good impact for its business, mudharabah financing has significant effecton the micro-enterprises performance, business experience has significant effect on the microenterprisesperformance, the age of the micro entrepreneurs has no significant effect on themicro-enterprises performance, the coaching does not strengthen the effect of mudharabahfinancing on the micro-enterprises performance, and the education of micro entrepreneurs doesnot strengthen the effect of business experience on the micro-enterprises performance.Keywords: Mudharabah Financing, Micro-Enterprises Performance, (BMT) Baitul Maal WatTamwil